Reliability evaluation method of distribution network considering the integration impact of distributed integrated energy system - Jianzhang Wu; Jianyong Zheng; Fei Mei; Kai Li; Xiaojing Qi (Energy Reports, 2022)
In modern power system, the connection between distribution network and distributed integrated energy system is becoming increasingly prevalent, which greatly influenced the operation strategy and reliability of the traditional distribution network. To evaluate the reliability of distribution network more precisely, a reliability evaluation method considering the integration impact of distributed integrated energy system is proposed. Firstly, the structure and mathematical model of the united energy system are described. Secondly, taking the minimum sum of operation and load reduction cost as the objective function, the optimal load reduction models of distribution network and distributed integrated energy system are established. Due to the interest game between these two systems, analytical target cascading theory is applied to deal with the decoupling of these two models. Thirdly, the reliability evaluation of the united system is performed based on Monte Carlo Simulation method. The simulation study of a modified IEEE RBTS system with a distributed integrated energy system indicates the effectiveness of the proposed method.